Systems Study on Railways and Roadways Transportation : 1978-79 Volume II Traffic Forecasting-Railways - Planning Commission (Planning Commission, 1975)
Growth of the Indian economy depends heavily on its transport sector. Though, the share of road transport in the movement of goods and passengers has been steadily increasing, railways still. Carry most of the bulk commodities comprising of industrial raw materials and essential consumer goods. Almost all the core sectors depend on the railways for the movement of their raw materials and finished products. Key to the success of the Fifth Five Year Plan is the fuller utilization of capacity of existing plants.
Planning Commission Government of India
Planning Commission Government of India